Audit Sistem Presensi Fingerprint di SMK Media Informatika Menggunakan Cobit 5 - Narti, Narti -; Muhasim, Muhasim (Evolusi : Jurnal Sains dan Manajemen, 2024)
Media Informatics Vocational School is one of the schools that has been implementing information technology for quite a long time by using a fingerprint tool to record the attendance of every teacher and education staff. However, in its implementation, the Media Informatics Vocational School has not yet carried out an audit of the information system. Due to these problems, the author discovered problems and wants to help the school in overcoming these problems. The purpose of audit system information is to show that the company procedures implemented are running correctly and functioning well. In this case the audit process uses the COBIT 5 framework as an implementation medium. Based on the analysis of the picture shown, there is a distance of 0.81 on the EDM02 sub domain, 0.29 on the BAI06 sub domain, 0.88 on the APO05 sub domain, 0.21 on the APO07 sub domain, 0.91 on the DSS01 sub domain, 0, 89 on the DSS03 subdomain, 0.74 on the DSS06 subdomain and 0.69 on the MEA01 subdomain. With an average gap of 0.66. The biggest gap is in the DSS01 sub domain of 0.91 and the smallest gap is in the APO07 sub domain of 0.21. And it was found that there was a gap with an average of 0.66 between the current implementation and the expected maturity level. The results of this research provide an overview of the effectiveness and efficiency of the fingerprint attendance information system at Media Informatics Vocational School as well as findings and recommendations for further improvement and development. It is hoped that this audit can help Media Informatics Vocational School improve their management and utilization of their attendance information system in accordance with COBIT 5 standards.